Graphene Oxide and Reduced Derivatives, as Powder or Film Scaffolds, Differentially Promote Dopaminergic Neuron Differentiation and Survival - Rodriguez-Losada, Noela; Wendelbob, Rune; Ocaña, M. Carmen; Casares, Amelia Diaz; Guzman de Villoría, Roberto; Aguirre Gomez, Jose A.; Arraez, Miguel A.; Gonzalez-Alegre, Pedro; Medina, Miguel A.; Arenas, Ernest; Narvaez, Jose A. (Frontiers in Neuroscience, 2020)
Emerging scaffold structures made of carbon nanomaterials such as graphene oxide (GO) have shown efficient bioconjugation with common biomolecules. Previous studies described that GO promotes the differentiation of neural stem cells and may be useful for neural regeneration. In this study, we examined the capacity of GO, full reduced (FRGO), and partially reduced (PRGO) powder and film to support survival, proliferation, differentiation, maturation, and bioenergetic function of a dopaminergic (DA) cell line derived from the mouse substantia nigra (SN4741). Our results show that the morphology of the film and the species of graphene (GO, PRGO or FRGO) influences the behaviour and function of these neurons. In general, we found better biocompatibility of the film species than that of the powder. Analysis of cell viability and cytotoxicity showed good cell survival, a lack of cell death in all GO forms and its derivatives, a decreased proliferation, and increased differentiation over time. Neuronal maturation of SN4741 in all GO forms, and its derivatives were assessed by increased protein levels of tyrosine hydroxylase (TH), dopamine transporter (DAT), the glutamate inward rectifying potassium channel 2 (GIRK2), and of synaptic proteins such as synaptobrevin and synaptophysin. Notably, PRGO-film increased the levels of Tuj1 and the expression of transcription factors specific for midbrain DA neurons such as Pitx3, Lmx1a, and Lmx1b. Bioenergetics and mitochondrial dysfunction were evaluated by measuring oxygen consumption modified by distinct GO species and were different between powder and film for the same GO species. Our results indicate that PRGO-film was the best GO species at maintaining mitochondrial function compared to control. Finally, different GO forms, and particularly PRGO-film was also found to prevent the loss of DA cells and the decrease of the α-synuclein (α-syn) in a molecular environment where oxidative stress has been induced to model Parkinson's disease. In conclusion, PRGO-film is the most efficient graphene species at promoting DA differentiation and preventing DA cell loss, thus becoming a suitable scaffold to test new drugs or develop constructs for Parkinson's disease cell replacement therapy.